Usaha Peningkatan Ekonomi Pengrajin Kayu Dalam Modernisasi Di Desa Balung Tutul, Kec. Balung, Kab. Jember - Vionata Gadis Ranika; Ainul Mutrofin; Esha Ayu Triana Waskita; Elanda Cika Alodya Nathania (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
This research is titled about the economic improvement of wood craftsmen in modernization in Balung Tutul Village, explaining the modernization of marketing technology used with qualitative research methods using a phenomenological approach. In the research, using Anthony Giddens' theory of modernity, which includes the transition of society towards modernization and the use of technology in an effort to improve the economy of wood craftsmen in their production.